Local enhancement of electron heating and neutral species generation in radio-frequency micro-atmospheric pressure plasma jets: the effects of structured electrode topologies. (22nd February 2023) - Liu, Yue; Vass, Máté; Hübner, Gerrit; Schulenberg, David; Hemke, Torben; Bischoff, Lena; Chur, Sascha; Steuer, David; Golda, Judith; Böke, Marc; Schulze, Julian; Korolov, Ihor; et al.
Abstract: The effects of structured electrode topologies on He/O2 radio frequency micro-atmospheric pressure plasma jets driven at 13.56 MHz are investigated by a combination of 2D fluid simulations and experiments. Good qualitative agreement is found between the computational and experimental results for the 2D spatio-temporally resolved dynamics of energetic electrons measured by phase resolved optical emission spectroscopy, 2D spatially resolved helium metastable densities measured by tunable diode laser absorption spectroscopy and 2D spatially resolved atomic oxygen densities measured by two photon absorption laser induced fluorescence. The presence of rectangular trenches of specific dimensions inside the electrodes is found to cause a local increase of the electron power absorption inside and above/below these surface structures. This method of controlling the electron energy distribution function via tailored surface topologies leads to a local increase of the metastable and atomic oxygen densities. A linear combination of trenches along the direction of the gas flow is found to result in an increase of the atomic oxygen density in the effluent, depending linearly on the number of trenches. These findings are explained by an enhanced Ohmic electric field inside each trench, originating from (a) the low electron density, and, consequently, the low plasma conductivity inside the trenches, and (b) the presence of a current focusing effect as a result of the electrode topology.